EVALUASI PENENTUAN DAN PEMANFAATAN PROGRAM JARING PENGAMAN BIDANG KESEHATAN - Sumaryanto Sumaryanto (LPPM UNY, 2001)
Abstract Social Protection Sector Development Programs is the one another of the efforts to resolving the economic crisis effects. Concern on the healthy status, specifically on behalf of destitute families, the sphere employing to be valued on the village’s midwife, Society Healthy Center until the next reconciliation for the hospitals. This research was purposed to understanding the precision of the target defining and benefiting by the receivers of the Social Protection Sector Development programs. The research’s work-area was in the Society Health center of Kalasan II at Purwomartani Village and at the Selomartani village, the Subdistrict of Kalasan of the Sleman Regency. The research kinds were the surveying with the data taking methods using the questionnaires. Finally, the data were analyzing using the percentage qualitative description analyst. The results shown where to defining of these Social Protection Sector Development Programs were appropriately matched on their receiver targets, and the receivers had been obtaining the benefits. The most purpose of the services was the basic medicinal treatments and the elucidation for the medical officials. Keywords: social, protection, sector, development, program